Demarcation area between juvenile and mature wood in Elaeocarpus angustifolius - Istie Rahayu; Gilang Laksono; Wayan Darmawan; Akhirudin Maddu; Esti Prihatini (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahayu I, Laksono GD, Darmawan W, Maddu A, Prihatini E. 2021. Demarcation area between juvenile and mature wood in Elaeocarpus angustifolius. Biodiversitas 22: 2583-2590. Wood for use in building and industrial materials is generally supplied from plantations and natural forests. Timber demand has been increasing as the population grows, but the availability of timber from natural forests is declining. Therefore, to meet timber needs, wood from community forests is becoming a solution. Community forests are widely planted with fast-growing trees, such as Elaeocarpus angustifolius Blume. It offers the advantages of a short cutting cycle and large-diameter wood. This study aimed to determine the demarcation area between juvenile and mature wood on 6-year-old E. angustifolius based on anatomical, physical, and mechanical properties. The parameters used to determine the demarcation area included the following properties: anatomical (fiber length, cell wall thickness, and microfibril angle [MFA]), physical (moisture content and green density), and mechanical (modulus of elasticity [MOE], modulus of rupture [MOR], and hardness). Those parameters were measured from pith to bark. Data analyses were based on segmented linear regression models using PROC NLIN in SAS. Fiber length, cell wall thickness, green density, MOE, MOR, and hardness values increased from pith to bark. Results from the segmented linear regression models on anatomical properties allowed extrapolating that mature wood would begin at the 18 cm (based on fiber length), the 20 cm (based on cell wall thickness), and the 21 cm (based on MFA) distance from the pith. the proportion of juvenile wood in E. angustifolius was 100%. Fiber length, cell wall thickness, and MFA can be used to determine the transition point of juvenile wood and mature wood in E. angustifolius.